Annuities for an Ageing World - Olivia S. Mitchell; David McCarthy (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2002)
Substantial research attention has been devoted to the pension accumulation process, whereby employees and those advising them work to accumulate funds for retirement. Until recently, less analysis has been devoted to the pension decumulation process – the process by which retirees finance their consumption during retirement. This gap has recently begun to be filled by an active group of researchers examining key aspects of the pension payout market. One of the areas of most interesting investigation has been in the area of annuities, which are financial products intended to cover the risk of retirees outliving their assets. This paper reviews and extends recent research examining the role of annuities in helping finance retirement consumption. We also examine key market and regulatory factors.
urn:nbn:de:hebis:30-18030
Keywords: 330; Alte Menschen; Einkommen; OECD-Staaten; Leibrente